Berberine prevents lethal EV71 neurological infection in newborn mice - Cui, Guangyi; Wang, Han; Yang, Chongting; Zhou, Xiaoxiao; Wang, Junyi; Wang, Tong; Ma, Tonghui (Frontiers in Pharmacology, 2022)
Enterovirus 71 (EV71) is the major pathogen causing fatal neurological complications of hand, foot, and mouth disease (HFMD) in young children. Currently no effective antiviral therapy is available. In the present study, we found that natural compound Berberine (BBR) displayed potent inhibitory effects on EV71 replication in various neural cells (IC50 of 2.79-4.03 M). In a newborn mouse model of lethal EV71 infection, BBR at 2-5 mg/Kg markedly reduced mortality and clinical scores. Consistently, the replication of EV71 and pathological changes were attenuated in various infected organs including brain and lung with BBR treatment. Interestingly, EV71 infection in the brain mainly localized in the peripheral zone of brainstem and largely in astrocytes. Primary culture of astrocytes from newborn mouse brain confirmed the efficient EV71 replication that was mostly inhibited by BBR treatment at 5 M. Further investigations revealed remarkably elevated cellular reactive oxygen species (ROS) levels that coincided with EV71 replication in primary cultured astrocytes and various cell lines. BBR largely abolished the virus-elevated ROS production and greatly diminished EV71 replication by up-regulating NFE2 like bZIP transcription factor 2 (Nrf2) via the kelch like ECH associated protein 1 (Keap)-Nrf2 axis. The nuclear localization of Nrf2 and expression of downstream antioxidant enzymes heme oxygenase 1 (HO-1) and NAD(P)H quinone dehydrogenase 1 (NQO1) were increased significantly by BBR treatment. Collectively, our findings revealed that BBR prevents lethal EV71 neurological infection via inhibiting virus replication through regulating Keap-Nrf2 axis and ROS generation in astrocytes of brainstem, thus providing a potential antiviral treatment for severe EV71 infection associated with neurological complications.